Penerapan Metode KMeans dan Cobweb Terhadap Analisis Prestasi Akademik Mahasiswa yang Mengikuti Kegiatan Kemahasiswaan - Neil Casaandra Sudharmono; Mewati Ayub (Jurnal Teknik Informatika dan Sistem Informasi, 2015)
The growth of an university can be seen with student’s academic records which can be used for determining students’ quality. Besides student’s academic records, other component that can be used to determine students’ quality is student’s participation in non-academic activities which most of universities have to develop their student’s softskill during their study period. Based on these data provision, we can analyze how non-academic activities affect student’s academic achievement. In this research, the data that used for analysis are students’ academic data and students’ activities data from Maranatha Christian University as case study. This analysis use one of data mining technique, which is clustering . The clustering method that used for this research are Kmeans andCobweb. Clustering method groups students and alumni that participate in student activities or not by looking and the student’s and alumni’s faculty, major, years of study, and if the student or alumni participate in student activites, we can analyze it with how many activities that the student and alumni had.